Albert & the whale Albrecht Dürer and how art imagines our world - Hoare, Philip 1958- (Pegasus Books, 2021)
Albert and the Whale explores the work of this remarkable man through a personal lens. Drawing on Philip's experience of the natural world, and of the elements that shape our contemporary lives, from suburbia to the wide open sea, Philip will enter Dürer's time machine. Seeking his own Leviathan, Hoare help us better understand the interplay between art and our world in this sublimely seductive book
Keywords: Dürer, Albrecht -- 1471-1528; Dürer, Albrecht / 1471-1528; Artists / Germany / Biography; Art / History; Art; Artists; Germany; Biographies; History